Multiwavelength observations of N 66 in the SMC: unveiling photodissociation interfaces and star formation - Rubio, M. (2000)
We present new observations of the major star-forming region N 66 in the Small Magellanic Cloud and of its surroundings, which add to those presented in Contursi et al. (citeContursi99, Paper I). High-sensitivity CO observations allowed the detection of molecular gas associated with the H i I region, for which a high-resolution image in [O iii ] lambda 5007 is presented. We also present images in the v(1-0) S(1) line of H_2 at 2.12 mu m and in the adjacent continuum. This material reveals an interesting photodissociation region. We show that the molecular gas that has not yet been photodissociated by the UV radiation of the stars is in hot, dense clumps with a very small surface filling factor. We discovered several embedded stars or stellar associations, and suggest that three successive stellar generations have already taken place in less than 3 million years. Based on observations with the Swedish-ESO Submillimeter Telescope (SEST) at the European Southern Observatory (ESO), La Silla, Chile, at the Cerro Tololo Interamerican Observatory, National Optical Observatories, operated by AURA under contract with the National Science Foundation, at the Las Campanas Observatory and with ISO, an ESA project with instruments funded by ESA member states (especially the PI countries: France, Germany, the Netherlands and the United Kingdom) and with the participation of ISAS and NASA.